Correlation between 12-hour and 24-hour urine total protein in pregnant women with preeclampsia - Adhikari, Shree Prasad; Pariyar, Jewan (Journal of Chitwan Medical College, 2019)
Background: Although 24-hour urine total protein (UTP) measurement is the gold standard method for detecting proteinuria in preeclamptic women, the procedure is lengthy and time consuming that might result in delay in diagnosis of the condition. This study aimed at determining the correlation between these 2 parameters. Methods: This was a cross-sectional study done on 50 pregnant women with preeclampsia admitted at Bharatpur Hospital from September 2018 - January 2019. Patient with preeclampsia and having albumin ≥1 on urine dipstick, the sample was collected in every 12 hours interval on two separate well labeled container with the assistance of nursing staff. Total urine protein at 12-hour and 24-hour were measured by spectrophotometric method. The data were analyzed using SPSS version 21. Correlation between the 2 measurements was analyzed using Spearman’s rank correlation coefficient. p<0.01 was considered to be statistically significant. Results: The age of participants ranged between 20-38 years (Mean age: 26.6 years). The maximum occurrence of preeclampsia was observed in primigravid women and younger age group (between 20-25 years), 72% had mild preeclampsia and 28% developed severe preeclampsia. There was a significant correlation between 12-hour and 24-hour UTP (Spearman’s r = 0.99, p<0.001). Conclusions: There is a strong correlation between 12- and 24-hour urine total protein measurements in women with preeclampsia. 12-hour UTP can be used as an alternative for the assessment of proteinuria in these women, with benefits such as early diagnosis and better patient compliance.